Smart Bolts Monitoring Using Wireless Sensor Network: Implementation and Performance Evaluation. (4th June 2014) - Baroudi, Uthman; Al-Roubaiey, Anas; Mekid, Samir; Bouhraoua, Abdelhafid; Garba, Yau
Abstract : Structural and industrial environments use hundreds to thousands of bolts to hold parts together. For most mechanical systems, the bolts are critical components because they are subject to axial tension triggering various failures; for example, compromised screw threadsand/or vibration caused untightening. Severe damages can result injury of personnel, equipment damage, and even loss of life. Typically, monitoring mechanical tension of the bolts is visually performed with red dot bolts or manually inspected, but this process is expensive in terms of effort, time, and money; additionally, perhaps the accessibility of the bolt itself is very difficult. Changing this tedious monitoring process to automated, quick, and precise process is our concern in this work. Nowadays, wireless sensor networks (WSN) have wide range of applications especially in surveillance and monitoring systems. In this paper, we propose an efficient and power-aware technique to monitor bolted joints using wireless sensor networks. Also, due to the randomization placement of bolts in real world, our proposed mechanisms have been studied with different deployment node distributions (grid, uniform, normal, and exponential). Furthermore, we have investigated different scenarios with different probability of bolt failures to explore their effect on power consumption and network lifetime.